Peran Ormas Muhammadiyah sebagai Faith-Based Organization dalam Memberikan Respons Kemanusiaan terhadap Rakyat Palestina - Olifiani, Laras Putri; Amal, Moh. Talabul (Indonesia Center for Middle East Studies, 2023)
The protracted conflict between Israel and Palestine, which is still unresolved, has resulted in hundreds of thousands of Palestinians being displaced and in dire need of humanitarian assistance. This issue become a great concern to all international relations actors, including religious organizations. This article will discuss the role of the religion-based organization, namely Muhammadiyah, in providing humanitarian assistance to the Palestinian community. The author uses qualitative research methods with an explanatory approach. Data collection was carried out using library research techniques, namely data collection techniques sourced from books, scientific journals, research reports, mass media news, and official documents. In analyzing the data, the author uses the concepts of “Muhammadiyah” and Faith-Based Organization. The findings of this research are that Muhammadiyah's activities related to Palestine consist of four dimensions, namely providing humanitarian assistance, developing the view that defending Palestine is part of Islamic activism, collecting humanitarian funds, and providing advocacy for Palestinian independence and increasing awareness of the Indonesian people about this issue.